Analysis of Land Use Suitability of The Krueng Aceh River in Banda Aceh City Area Using Geographical Information Systems - Zalmita, Novia; Samudra, Muhammad Yorgi; Rosali, Ely Satiyasih; Izzati, Fatini Nur (Universitas Negeri Medan, 2025)
Indonesia owns many rivers, with at least 5,590 main rivers and 65,017 tributaries. Indonesian Government requires a minimum 10 meters of open land areas (borders) on the left and right sides of the river. However, this regulation is not easy to apply since not all rivers have land suitability that meet the requirements. This study seeks to reveal the suitability of land use in the watershed area of the Krueng Aceh in accordance with Government Regulation number 38 article 9 of 2011 concerning rivers. This study uses a Geographic Information System with quantitative approach with data sourced from government-owned databases such as the Geospatial Information Agency (BIG). Data processing is done by Overlay and Buffering technique. The results of the study show that: (1) Overall, the border of the Krueng Aceh is 260,291 m2 which covers six districts in Banda Aceh City. (2) In four of the six districts through which the Krueng Aceh watershed flows, there are buildings standing in the river border area. (3) Districts with a level of suitability for land use in the Krueng The lowest Aceh is Kuta Raja District (40.7%). The district with the highest percentage of suitability for land use is the Syiah Kuala District (98.9%). (4) The total percentage of suitability for land use in the Krueng Aceh is 81% or covers an area of 210,836 m2. (5) The land use of the border of the Krueng Aceh area has not experienced a significant land conversion into a residential area.